KURANGNYA KETERAMPILAN BERTANYA SISWA PADA PEMBELAJARAN PPKn KELAS VI DI SDN GN.PICUNG 04 - Ashri Pratiwi; Reksa Adya Pribadi; Ujang Jamaludin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the problem of the lack of questioning skills ofstudents with a student population of 40 people, in class IV Civics learning at SDNegeri Gn. Picung 04. This research uses the evaluation method where theresearcher will evaluate the problems that exist in a class in their learning andprovide solutions to overcome problems, in learning asking skills is an importantfactor in active learning, therefore the researcher chooses a planted questionstrategy combined with the learning method. problem based learning. Plantedquestions are used as a medium for student discussion by asking fellow studentsin the class with the material presented in the form of problems that often occur ineveryday life. In applying these strategies and methods, an increase in the numberof students asking as much as 34%.